Some rare species of the genera Amphidelus and Aporcelaimellus (Nematoda: Dorylaimida) from Sas Hill, Budapest, Hungary - Kiss, M. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2009)
Four rare nematode species from Sas Hill in Budapest are described and illustrated. They are Amphidelus lagrecai Vinciguerra & De Francisci, 1973, Amphidelus coluber Andrássy, 1973, Aporcelaimellus alius Andrássy, 2002 and Apor¬ce¬laimellus amylovorus (Thorne & Swanger, 1936) Heyns, 1965. Of them, A. lagrecai is new to the fauna of Hungary.